2011
DOI: 10.1097/pcc.0b013e3181e2a4fe
|View full text |Cite
|
Sign up to set email alerts
|

Potential pediatric intensive care unit demand/capacity mismatch due to novel pH1N1 in Canada

Abstract: Reducing the attack rate among children, whether through vaccination or additional measures, such as social distancing, will be critical to ensure sufficient pediatric intensive care unit capacity for continued pediatric care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…This study showed that if the attack rate was higher than 15%, significant PICU shortages would be expected to occur. However, this did not occur during the first or second wave -the attack rate was estimated at approximately 10% [51]. There were enough beds and mechanical ventilators in Canadian PICUs to provide critical care despite a 3% increase in admissions.…”
Section: Disease Burden On Healthcare Resourcesmentioning
confidence: 91%
See 1 more Smart Citation
“…This study showed that if the attack rate was higher than 15%, significant PICU shortages would be expected to occur. However, this did not occur during the first or second wave -the attack rate was estimated at approximately 10% [51]. There were enough beds and mechanical ventilators in Canadian PICUs to provide critical care despite a 3% increase in admissions.…”
Section: Disease Burden On Healthcare Resourcesmentioning
confidence: 91%
“…Some studies performed using data from the first wave suggested a possible mismatch between resources (e.g., ventilators and PICU beds) and care demands [50,51]. To improve forecasting, it will be necessary to improve real-time data collection and further delineate geography-and population-specific risks.…”
Section: Adaptation Of Health Resources To Pandemic Burdenmentioning
confidence: 97%
“…Family practitioners provide primary health care in each country and most vaccine delivery does not require out-of-pocket payment. The number of PICU is also similar (2.9 bed/100000 children under 15 years in Canada and 2.5 beds per 100000 children in France)[9,13]. During the pandemic, treatment recommendations were the same, those of the World Health Organization.…”
Section: Methodsmentioning
confidence: 99%
“…This approach may serve as a resource multiplier and may allow CSC to be instituted for shorter periods of time. Furthermore, in certain pandemics, younger children may be more vulnerable to respiratory failure and modeling for the younger age, and varying duration of infection and vaccination rates will be needed depending on the infectious agent to determine when CSC should be instituted (13). The outcome predictors model is not perfect.…”
mentioning
confidence: 96%